Including GLBTIQ Student Rights in ‘Human’ Rights Education .......... 137 - Jones, Tiffany (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
Discrimination against gay, lesbian, bisexual, transgender, intersex and otherwise queer (GLBTIQ) students has recently become a key area for global attention in human rights education. The inclusion of GLBTIQ issues in anti-discrimination efforts in schools has been particularly aided by events held by the United Nations that specifically cam-paigned against homophobic bullying, speeches by the UN Secretary General framing homophobic bullying as “a public health crisis”, and UNESCO’s recent dissemination of new policy, programming and practice guidance to education sectors around the world. The movement towards protecting GLBTIQ students against bullying and discrimination, and the provision of structural and social supports in schools, has the potential to impact how diverse sexualities and gender identities are understood generally. This paper uses a Critical Discourse Analysis to provide an overview of constructions of GLBTIQ students in education policies and practices around the world, in order to set the context for the ap-proaches promoted in UNESCO’s (re)construction of human rights education today. Four main orientations to GLBTIQ students found both historically and in education sectors around the world today are detailed: conservative, liberal, critical and post-modern orien-tations. Within each orientation, a number of views on GLBTIQ students are described in relation to the broader discourses on sexuality within which they were formed. The paper argues that the public dissemination of evidence of verbal and physical homophobic abuse in schools, the prevalence of self-harm and suicides associated with homophobic bully-ing, and the impact of anti-homophobia education policies in reducing such problems have been key to the shift in understanding the position of GLBTIQ students in human rights education in places where anti-homophobia legislation and education policies ex-ist. It gives examples from various countries of how this public dissemination – whether through courts of law, research reports, or media coverage – has been an important cata-lyst for change. The framing of GLBTIQ students as potential victims of discrimination at school (rather than as deviants, non-existent or biological aberrations for example) is thus argued as central to the promotion of ‘Anti-discrimination’, ‘Safe and Supportive Schools’ and ‘Inclusive Education’ approaches found in new human rights movements. While por-traying young people as “victims” is certainly not ideal in the long-term, it is nevertheless one key step in “humanising” GLBTIQ students enough to break down social and political barriers to their inclusion in constructions of ‘human’ rights educational provisions.